EFEKTIVITAS MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI SMA - Fakhriyati, Anis; Buwono, Sri; Adlika, Nur Meily (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine differences in learning outcomes of the control class and the experimental class using the mind mapping learning model with the imindmap application. The type of research used is a quasi experimental. Design type nonequivalent control group design. Data collection techniques used are observations and measurement. The data collection instruments in this study were test sheets and observation sheets. The results of this study indicate that there are differences in the learning outcomes of students who are taught using mind mapping learning model with the imindmap application and students who are not taught using mind mapping learning model with the imindmap application.